Synthesis, Characterization and Antimicrobial Evaluation of Some New 1, 3, 4-oxadiazoline Compounds - Khaldoon S. Alhadad (Journal of Global Pharma Technology, 2016)
This study involve synthesis of some new 1,3,4-oxadiazoline compounds and screening the antibacterial activity against Staphylococcus aureus , Escherichia coli and pseudomonas aeruginosa bacteria and the antifungal activity against Aspergillus flavus and Candida albicans. The structures of newly prepared compounds (5a-5f) were confirmed by spectroscopic methods like elemental analysis (CHN), FT-IR and 1H-NMR spectroscopy. All the compounds showed good antibacterial activity as compared with the standard drugs (cefepime and amoxicillin) against Staphylococcus aureus , Escherichia coli and pseudomonas aeruginosa while the compounds (5a, 5b, 5c and 5d) displayed a good inhibition zone of growth against Aspergillus flavus and Candida albicans.Keywords: 1, 3, 4-oxadiazoline, Antimicrobial, Heterocyclic compounds, Hydrazone derivatives.